DIVERSION CONDUCTED BY THE PROSECUTOR IN THE CRIME OF THEFT WITH AGGRAVATION IN JUVENILE OFFENDERS - Yopan Apriana, Acep; Martinesya, Sefa; Bustomi, Bustomi (Fakultas Hukum Universitas Swadaya Gunung Jati, 2023)
Diversion is an effort that must be carried out by law enforcement, both by Investigators, Public Prosecutors, and Judges, in order to protect children in conflict with the law. However, efforts to implement diversion must also be accompanied by considerations from Bapas who conduct research and assistance to children in conflict with the law. The purpose of this study is to determine the criminal law review of the diversion carried out by the Public Prosecutor in the crime of aggravated theft of child offenders, as well as to determine the juridical implications of the diversion carried out by the Public Prosecutor in the crime of aggravated theft of child offenders. The method used in this research is normative juridical method, with the nature of descriptive research, then data collection sourced from secondary data, and then the data is processed qualitatively. The results showed that: (1) The criminal law review of the diversion carried out by the Public Prosecutor in the crime of theft with aggravation on child perpetrators is basically not in accordance with the provisions in Article 7 paragraph (2) of the SPPA Law, because diversion can only be implemented with the provisions threatened with imprisonment under 7 (seven) years, while the three child perpetrators committed a criminal offense with aggravation stipulated in Article 363 paragraph (1) points 4 and 5 of the Criminal Code which carries a penalty of more than 7 (seven) years in prison. However, if seen from the provisions in Article 2 and Article 3 of the Child Protection Law, then of course diversion should be carried out by the Public Prosecutor, considering that the three child perpetrators have never committed a criminal offense before; (2) The juridical implications of the diversion carried out by the Public Prosecutor in the crime of theft with aggravation on child perpetrators, which resulted in the refusal of the Bapas to sign the diversion agreement on the grounds that the diversion effort has violated the provisions of Article 7 paragraph (2) of the SPPA Law